A Long-Term Enriched Environment Ameliorates the Accelerated Age-Related Memory Impairment Induced by Gestational Administration of Lipopolysaccharide: Role of Plastic Mitochondrial Quality Control - Zhuang, Zhan-Qiang; Zhang, Zhe-Zhe; Zhang, Yue-Ming; Ge, He-Hua; Sun, Shi-Yu; Zhang, Ping; Chen, Gui-Hai (Frontiers in Cellular Neuroscience, 2021)
Previous research has shown that gestational infection accelerates age-related memory impairment in mother mice. Enriched environment (EE) can improve age-related memory impairment. Mitochondrial dysfunction is implicated in brain aging pathogenesis. Disruption of mitochondrial quality control (MQC) worsens mitochondrial dysfunction. However, it is uncertain whether EE counteract accelerated age-related memory impairment which induced by gestational infection and whether this process is associated with alterations in MQC. In this study, CD-1 mice (gestational days 15–17) intraperitoneally received lipopolysaccharide (LPS, 50 μg/kg) or normal saline (CON group) daily. The mothers were separated from her children After stopping normal lactation, the mothers received LPS were divided into LPS and LPS-E groups based on whether the EE was given until the end of the experiment. At the ages of 6 and 18 months, Morris water maze tasks was used to evaluate spatial learning and memory abilities. The transmission electron microscope was utilized for the morphological observation of mitochondria. RT-qPCR and western blot were employed to measure the MQC-related mRNAs and proteins in the hippocampus, respectively. Results showed all the aged mice had striking decline of spatial learning and memory performances, obvious changes in mitochondrial morphology and decreased mRNA/protein levels of mitochondrial dynamics (Mfn1/Mfn2, OPA1, Drp1), biogenesis (PGC-1α), and mitophagy (PINK1/Parkin) in hippocampus than the young mice. The LPS treatment exacerbated the decline of age-related spatial learning and memory and accelerated the reduction of the MQC-related mRNAs and proteins, but increased PGC-1α levels in the young group. The LPS-E treatment could alleviate the accelerated decline of age-related spatial learning and memory and ameliorated the MQC-related mRNA or protein alterations than the LPS treatment, especially in aged groups. In conclusion, long-term EE can counteract accelerated age-related cognitive impairment by modulating MQC in CD-1 mother mice exposed to LPS during pregnancy.